Anisotropic response of surface circulation to wind forcing, as inferred from high‐frequency radar currents in the southeastern Bay of Biscay. Issue 4 (18th April 2015) - Fontán, Almudena; Cornuelle, Bruce
Abstract The short‐term (less than 20 days) response of surface circulation to wind has been determined in waters of the southeastern Bay of Biscay, using wind impulse response (time domain) and transfer (frequency domain) functions relating high‐frequency radar currents and reanalysis winds. The response of surface currents is amplified at the near‐inertial frequency and the low‐frequency and it varies spatially. The analysis indicates that the response of the ocean to the wind is slightly anisotropic, likely due to pressure gradients and friction induced by the bottom and coastline boundaries in this region. Thus, the transfer function at the near‐inertial frequency decreases onshore due to the coastline inhibition of circularly polarized near‐inertial motion. In contrast, the low‐frequency transfer function is enhanced toward the coast as a result of the geostrophic balance between the cross‐shore pressure gradient and the Coriolis forces. The transfer functions also vary with season. In summer, the current response to wind is expected to be stronger but shallower due to stratification; in winter, the larger mixed layer depth results in a weaker but deeper response. The results obtained are consistent with the theoretical description of wind‐driven circulation and can be used to develop a statistical model with a broad range of applications including accurate oceanic forecasting and understanding of the coupled atmosphere‐ocean influence on marine ecosystems.